NUTRITION STATUSAND COGNITIVE DEVELOPMENT IN TODDLER - Tri Peni; Windu Santoso; Octavia Ayu pudji Utami (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Toddler is the most important step of all stages of development. Children of this age have tremendous potential, but the potential will arise when it comes to adequate care, health, attention, affection and education. Malnutrition in early childhood, has an impact on low cognitive abilities. The purpose of this research was to determine the correlation of nutritional status with cognitive development in toddler age children in Mojowates Rejo Village, Kemlagi Sub-district, Mojokerto Regency. The research method was analytic correlation with cross sectional approach. The population in this research were all children of toddler age in Mojowates Rejo Village Kemlagi Sub-district Mojokerto Regency in May 2017 as many as 62 children. Sampling technique used purposive sampling. The sample size were 59 people. The results of this research suggested that more than a half (61.5%) of children with obese nutritional status had good cognitive development, more than a half (61.9%) of children with normal nutritional status had adequate cognitive development, and the majority (100%) Children with thin nutritional status had less cognitive development. Data analysis used in this research was Spearman's rho test with result of Ï value was 0,010 or lessthan Î± (0,05), so H1 is accepted, meantthat there was correlation between nutritional status with cognitive development in toddler age children in Mojowates Rejo Village Kemlagi Sub-district Mojokerto Regency. Parents should provide balanced nutritional intake, control child feeding to avoid obesity, buy educative games to stimulate child development, teach nannies about stimulating child development and allow children to explore the environment without ignoring it.